(3GdCSQGQ GdcejfI aj Gdcjfg cjfgs - (3MSjf Hf Ydj Hf SdjeGf GdMfaj, GdeYQha HGdTjN MSjf NhLg,J (B1169 (3g` s
(3ChdgG (B:s
(3CeG HYO Efg bO SHb di eMfI HHdGO GdEaQfL hGLJeYJ eY GdHYV ef MceGFgG hfbdJ Yfg ahGFO dWjaI hCehQkG , NUhUkG ai GdOhGA GdeYQha HGdcjfg cjfg s
(3BNQgG (B:s
(3aEPG JbGjG aef GdZO jSbi Gdcjfg cjfg deQjV GdMei , ajMUd HgG GdTaGA YGLdG HMhd Gddg , hGddg GdTGai s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HYV cdeGJgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B248 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B31s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B20 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdOcJhQ CMeO Hf ejdGO GdNGUI HJhfS s
Keywords: (3GdWHs